Persepsi Orang Tua Terhadap Praktik Disiplin Di Madrasah Ibtidaiyah - Mochammad Ramdan Samadi; Laesti Nurishlah (TA'DIB: Jurnal Pendidikan Agama Islam, 2023)
Discipline is an effort to shape children's character and habits. The implementation of discipline in schools is carried out using a systematic, consistent and measurable method. The study aimed to find out what parents think about the way schools handle teaching children to behave correctly, with a focus on whether the methods used, such as rewards or punishments, are seen as effective by parents. This research was written using a qualitative method of literacy study from various sources. The research results show that involving students in making rules and improving communication between schools and parents can help in better managing children's behavior.